1994
DOI: 10.1002/ajim.4700260203
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to chlorinated aliphatic hydrocarbons and risk of astrocytic brain cancer

Abstract: Chlorinated aliphatic hydrocarbons (CAHs) were evaluated as potential risk factors for astrocytic brain tumors. Job-exposure matrices for six individual CAHs and for the general class of organic solvents were applied to data from a case-control study of brain cancer among white men. The matrices indicated whether the CAHs were likely to have been used in each industry and occupation by decade (1920-1980), and provided estimates of probability and intensity of exposure for "exposed" industries and occupations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
1
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 32 publications
1
62
1
1
Order By: Relevance
“…These include studies of bladder cancer (12,(42)(43)(44)(45), brain cancer (46,47), buccal and oral cancers (48,49), childhood brain cancer (47), childhood leukemia (50) …”
Section: Case-control Studiesmentioning
confidence: 99%
“…These include studies of bladder cancer (12,(42)(43)(44)(45), brain cancer (46,47), buccal and oral cancers (48,49), childhood brain cancer (47), childhood leukemia (50) …”
Section: Case-control Studiesmentioning
confidence: 99%
“…Several studies have observed an increased risk of brain tumors in association with work in the textile industry (2-7), although no specific causative agents have been identified. Studies of other industries have found associations between brain tumors and several exposures commonly encountered in the textile industry, including electromagnetic fields (EMF) [see Kheifets (8) and Ahlbom (9) for reviews], solvents (10)(11)(12), metals (10,13,14), and lubricants (15)(16)(17).…”
mentioning
confidence: 99%
“…The solvents derived from chlorinated aliphatic hydrocarbons such as tetrachloroethylene, trichloroethylene, carbon tetrachloride, monochloromethane, trichloroethane and dichloromethane are carcinogenic agents 8,9,27,29,30 . In the case-control study, performed by Heinemann et al 29 , six solvents derived from chlorinated aliphatic hydrocarbons, with mutagenic actions, had shown high significant association among astrocytomas and methyl chloride, in a matrix of occupational exposure.…”
Section: Discussionmentioning
confidence: 99%